Cardio-respiratory failure secondary to ectopic Cushing's syndrome as the index presentation of small-cell lung cancer. (14th August 2013) - von Stempel, Conrad; Perks, Clarissa; Corcoran, John; Grayez, Jamal
Abstract : A 79-year-old woman, a smoker, presented to the emergency department with a 2-week history of progressive dyspnoea and peripheral oedema, preceded by flu-like symptoms that had failed to improve despite antibiotics. Examination identified severe hypertension and signs consistent with severe fluid overload. Baseline chest X ray showed a right-sided abnormality. In the context of an extensive smoking history CT thorax was indicated which demonstrated a right-sided hilar mass and lymphadenopathy. Blood tests showed an unexplained metabolic alkalosis with partial respiratory compensation and hypokalaemia prompting endocrinological tests investigating Cushing's syndrome. Urinary cortisol was measured at 3174 nmol/L/24 h (normal<560), serum adrenocorticotropic hormone (ACTH) of 215 ng/L (normal<46). Pleural fluid cytology confirmed a diagnosis of small-cell lung cancer (SCLC). The patient's condition deteriorated despite intravenous diuretics and nitrates, metyrapone and non-invasive ventilation. Treatment was withdrawn 1 week after admission. The clinical course in the presence of biochemical derangement and SCLC is highly suggestive of paraneoplastic ectopic ACTH secretion.